(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify the guidance needs of high-achieving and underachieving female students in secondary schools. To achieve the research objective, the researcher designed a scale of 81 items to measure the guidance needs with three domains administered to 400 male and female students selected randomly from secondary schools in Baghdad for the academic year 2023-2024. The results showed that high-achieving female students had social and achievement counseling needs. The underachieving female students had social and psychological counseling needs. The first intermediate students also showed social and achievement needs but did not show psychological needs. The results indicated that there were statistical differences according to academic achievement in favor of high-achieving female students. The research recommends working to provide specialized psychological and educational counseling centers affiliated with the Ministry of Education to help students to get rid of problems and negative extremist tendencies.